Eiders as Long Distance Connectors in Arctic Networks. (July 2019) - Vestbo, Stine; Hindberg, Claus; Olesen, Jens M.; Funch, Peter
As hunters and gatherers, humans have always exploited a wide variety of natural resources. Hunting, in particular, focuses upon individual species. The relationships between human and game are most often seen as isolated entities, for example, human–bison, human–whale, human–seabird or human–mammoth. However, hunting interactions are embedded in large and complex ecological networks. Seabirds such as the common eider ( Somateria mollissima ) have been and are still being hunted by both indigenous people of the Arctic and Europeans. Due to anthropogenic pressures, including hunting, several common eider populations have declined during the 20th century, even as much as up to 10-fold. Here, we review the ecological role of the common eider in Arctic networks and the diversity of human–eider interactions, underlining its importance for both humans and nonhumans. We place these interactions in a wider ecological context and discuss how human activities affecting eiders propagate through the Arctic ecological network and can cause far-reaching ecological effects.